2014
DOI: 10.1371/journal.pone.0109128
|View full text |Cite
|
Sign up to set email alerts
|

TMEM43 Mutation p.S358L Alters Intercalated Disc Protein Expression and Reduces Conduction Velocity in Arrhythmogenic Right Ventricular Cardiomyopathy

Abstract: Arrhythmogenic right ventricular cardiomyopathy (ARVC) is a myocardial disease characterized by fibro-fatty replacement of myocardium in the right ventricular free wall and frequently results in life-threatening ventricular arrhythmias and sudden cardiac death. A heterozygous missense mutation in the transmembrane protein 43 (TMEM43) gene, p.S358L, has been genetically identified to cause autosomal dominant ARVC type 5 in a founder population from the island of Newfoundland, Canada. Little is known about the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 66 publications
0
46
0
Order By: Relevance
“…This finding has been confirmed in independent studies and has been seen in association with mutations in all of the desmosomal genes as well as in patients who fulfill diagnostic criteria for ACM but in whom no desmosomal mutation can be detected. 43, 44 Reduced plakoglobin signal at intercalated disks has also been reported in ACM patients from Newfoundland bearing the S358L mutation in TMEM43 45 and ACM patients from the Netherlands bearing the R14del mutation in PLN (but not in patients with the same PLN mutation but who present with a DCM phenotype). 31 Thus, reduced junctional signal for plakoglobin appears to track with the disease phenotype.…”
Section: Molecular Pathology Of Acmmentioning
confidence: 86%
“…This finding has been confirmed in independent studies and has been seen in association with mutations in all of the desmosomal genes as well as in patients who fulfill diagnostic criteria for ACM but in whom no desmosomal mutation can be detected. 43, 44 Reduced plakoglobin signal at intercalated disks has also been reported in ACM patients from Newfoundland bearing the S358L mutation in TMEM43 45 and ACM patients from the Netherlands bearing the R14del mutation in PLN (but not in patients with the same PLN mutation but who present with a DCM phenotype). 31 Thus, reduced junctional signal for plakoglobin appears to track with the disease phenotype.…”
Section: Molecular Pathology Of Acmmentioning
confidence: 86%
“…Moreover, XPC (p = 8.3 10 -15 ) and SLC6A6 (p = 6.9 10 -6 ) LV expressions were significantly increased in DCM patients compared to healthy donors ( Supplementary Table 7A) while LSM3 expression was significantly decreased (p = 7.6 10 -8 ). Functional candidate at this locus may include TMEM43, implied in arrhythmogenic right ventricular cardiomyopathy (ARVC) (39)(40)(41), and SLC6A6, for which a homozygous deletion affecting a splice site was found by whole-exome sequencing in a patient with idiopathic DCM (42).…”
Section: Heritabilitymentioning
confidence: 99%
“…23 Murine cell studies have shown that the S358L missense mutation alters the localisation of intercalated disc proteins, changes gap junction function and reduces conduction velocity. 41 However, the mechanism by which this pathogenic variant causes ARVC is poorly understood at present.…”
Section: Pathophysiologymentioning
confidence: 99%